Al-Shāfiʿī’s position on analogical reasoning in Islamic criminal law: human rights implications - Zakariyah, Luqman (2013)
Al-Shāfiʿī (d.204/820) has been unreservedly credited as one of the designers, if not the “master architect,” of uṣūl al-fiqh (Principles of Islamic jurisprudence). His most important scholarly work, Al-Risālah (The Epistle), clearly demonstrates his cognitive creativity in this field. One of the methodologies for the decision of cases under Islamic law that Al-Shāfiʿī championed is qiyās(analogical reasoning), which he equated with ijtihād (legal reasoning). His swinging approach on the use of qiyas in criminal law invites further enquiry into the locus standi of qiyās in general and in criminal law in particular. The extent to which qiyās can be applied to Islamic criminal law depends upon the degree or typology of qiyās being used, taking into account the Islamic theory of criminology. This paper will analyze the position of al-Shāfiʿī in this regard. It will critically examine al-Shāfiʿī’s complex views on the use of qiyās as a method for establishing culpability under Islamic criminal law. This will be done through his two famous literature al-Umm and al-Risalah. It will then explore how his position corresponds to the human rights paradigm in the contemporary age. The paper will tentatively concludes that, while the use of qiyās in Islamic criminal law, especially in law of retaliation (qiṣāṣ) and predetermined punishments (ḥudūd) in accordance with al-Shāfiʿī’s approach is tantamount to incriminating a person based on less than certainty (yaqīn), it also represents the most promising way of protecting human rights from the objectives of Islamic law (maqasid al-shariah).